Landscape change and landscape fragmentation analysis in Jeli, Kelantan - Latipah Muhammad Shah (2019)
Landscape changes have many positive and negative impacts, it is all depends on rates of changes, planning policies and others factors that contribute in landscape changes and fragmentation. This paper main intends to quantify the landscape change in Jeli in 1994, 2004, and 2014 also to determine the degree of landscape fragmentation in Jeli in that three particular years. The landscape changes were based on the LULC. The spatial and transition changes of each LULC were analysed by using the landscape change analysis and landscape structure analysis for each landscape metric in 1994, 2004 and 2014. From the analysis it shows that the landscape change happened in Jeli for the three years periods. Jeli experienced the fragmentation of forest vegetation due to built-up. In 1994 and 2004 there was 57.34% forest loss meanwhile in 2004 and 2014 the forest vegetation loss due to built-up was 8.87%. The landscape structure that shows the Jeli area was fragmented during that period of time was from the value of the landscape structure analysis PD, LPI, MPA, LSI, ENN, and PAREA. In conclusions forest vegetation in Jeli had been experiencing landscape changes due to the increased of the anthropogenic activities.